Size Distribution of Mangrove Crabs (Scylla spp.) Caught By Fishermen in the Bagek Kembar Exclusive Ecosystem Area (KEE), Sekotong, West Lombok - Lina Sapta Laraswati; Abdul Syukur; Karnan Karnan; H. Mahrus (Jurnal Pijar MIPA, 2025)
Mangrove crab (Scylla spp.) is one of the fishery commodities of high economic value that depends on the existence of mangrove ecosystems. The Bagek Kembar Exclusive Ecosystem Area (KEE) in Sekotong, West Lombok, is one of the important habitats for mangrove crabs and serves as the primary location for fishing activities by local fishermen. This study aims to determine the distribution of mangrove crab size caught by fishermen based on morphometric parameters, which include carapace length, carapace width, abdomen width, propodus length, propodus width, merus length, dactylus length, and plepod diameter. This type of research uses a descriptive research design with a quantitative approach. Sampling was conducted using purposive sampling, where mangrove crabs caught by fishermen at the research site were considered a representative sample of the population. Data analysis was conducted using descriptive statistics, which included calculating mean values, median, mode, and standard deviation, as well as analysing the frequency distribution of mangrove crab sizes. The determination of the number of classes and the interval of the frequency distribution class was carried out using Sturges' rule formula to describe the population structure of mangrove crabs. The study's results showed that most of the mangrove crabs caught were small to medium in size. The majority (65%) of crabs have a carapace length (PK) between 4–6 cm and are dominated by the juvenile or premature gonadal phase. The rarity of large individuals (>10 cm) suggests that crabs are significantly exploited before reaching their maximum adult size. This pattern also shows the role of KEE Bagek Kembar as a nursery ground dominated by juvenile individuals. Based on these findings, management efforts such as determining minimum catch sizes, protecting nursery habitats, increasing fishing gear selectivity, and long-term population monitoring are recommended to support the sustainability of mangrove crab stocks in this region.